Zero leprosy strategic plans: Global and national level: A short communication - K Geetha (Wolters Kluwer Medknow Publications, 2024)
Since the launch of multidrug therapy in 1982, the global leprosy situation has undergone significant changes, with the prevalence falling from over 5 million cases in the mid-1980s to <200,000 by the end of 2016. In India, the program reduced the prevalence rate from 57.8/10,000 in 1983 to <1/10,000 by the end of 2005, marking the achievement of the World Health Organizations (WHOs) target of eliminating leprosy as a public health issue. The WHO has recently introduced a new global leprosy plan called "Towards Zero Leprosy" as part of the disease-specific strategies outlined in the WHO's roadmap for neglected tropical diseases (NTDs) 2021-2030. This strategy aims to achieve interruption of leprosy transmission by 2030 and provides a framework for direction, objectives, challenges, and strategic pillars at a global level. In India, a committee of over 80 experts in the field of leprosy developed the National Strategic Plan and Roadmap for Leprosy 2023-2027, which was published on January 30, 2023. This policy is aligned with the WHO's NTDs roadmap 2021-2030 and the Global Leprosy Strategy 2021-2030, both of which aim to interrupt leprosy transmission by 2030. In this article, we have discussed the strategic plans of both the National leprosy eradication programme (NLEP) and the WHO.